Indicators of asthma control among students in a rural, school-based asthma management program. (October 2014) - Rasberry, Catherine N.; Cheung, Karen; Buckley, Rebekah; Dunville, Richard; Daniels, Brandy; Cook, Deborah; Robin, Leah; Dean, Blair
Abstract Objective: The evaluation sought to determine if a comprehensive, school-based asthma management program in a small, rural school district helped students improve asthma control. Methods: To determine if students in the asthma program demonstrated better asthma control than students in a comparison school district, the evaluation team used a quasi-experimental, cross-sectional design and administered questionnaires assessing asthma control (which included FEV1 measurement) to 456 students with asthma in the intervention and comparison districts. Data were analyzed for differences in asthma control between students in the two districts. To determine if students in the intervention experienced increased asthma control between baseline and follow-up, the evaluation team used a one-group retrospective design. Program records for 323 students were analyzed for differences in percent of predicted forced expiratory volume in one second (FEV1) between baseline and follow-up. Results: Students with asthma in the intervention district exhibited significantly better asthma control than students with asthma in the comparison district. Percent of predicted FEV1 did not change significantly between baseline and follow-up for the intervention participants; however, post hoc analyses revealed students with poorly controlled asthma at baseline had significantly higher FEV1 scores at follow-up, and students with well-controlled asthma at baseline had significantly lower FEV1 scores at follow-up. Conclusions: Findings suggest that the comprehensive school-based program led to improvements in asthma control for students with poorly controlled asthma at baseline, and school-based programs need mechanisms for tracking students with initially well-controlled asthma to ensure they maintain control.